Lyman H. Legters, ed.: The German Democratic Republic: A Developed Socialist Society - John T Walker (GDR Bulletin, 1980)
Boulder, Colo.: Westview, 1978. (Westview Special Studies on the Soviet Union and Eastern Europe), xi and 285 p.